Adsorptive Properties of Biochar Derived from Sago Effluent Activated Sludge Process - Siti Nur Aqilah, Makshut (UNIMAS, 2022)
Bioconversion of agricultural wastes into value-added products provides an eco-friendly alternative for a sustainable waste management system. In this study, activated carbon (AC) derived from the sago effluent activated sludge process was proposed for the removal of lead(II) (Pb(II)) and methylene blue (MB) dye from an aqueous solution. Sago effluent activated sludge was pyrolyzed in a tube furnace and underwent chemical activation with NaOH to yield sago AC. Batch experiments were used to study the Pb(II) adsorption by sago AC at adsorbent dosage (0.1 – 0.5 g), initial Pb(II) concentration (1 – 5 mg/L), and pH (2 – 10), and MB adsorption at initial MB concentration (2 – 10 mg/L) and contact time (30 – 90 min). Response surface methodology (RSM) with central composite design (CCD) was used to optimize the adsorption of Pb(II) and MB. Results showed that the AC has a large pore size (2.70 – 6.90 μm) and a surface area of 78.863 m2/g. Adsorption of Pb(II) and MB can be represented by Langmuir isotherm with R2 values of 0.9308 and 0.9225 respectively. The optimum Pb(II) removal (99.87%) occurred at pH 2, 0.5 g adsorbent dosage, 5 mg/L initial Pb(II) concentration and at 30 min. The optimum MB removal (92.69%) occurred at pH 6, 10 mg/L initial MB concentration, 0.5 g adsorbent dosage, and 60 min. In conclusion, sago AC derived from the sago effluent activated sludge process is an excellent adsorbent for Pb(II) and MB.